The Integration of Artificial Intelligence in Indonesian Language Learning: Pedagogical Opportunities and Risks - Muh. Safar; Rustiyana Rustiyana (PT. Anagata Sembagi Education, 2025)
The rapid development of artificial intelligence (AI) has significantly transformed educational practices, including Indonesian language learning. AI offers various pedagogical opportunities such as personalized learning, enhanced literacy skills, and continuous feedback, while simultaneously posing risks that may undermine the core values of language pedagogy. This study aims to critically analyze the pedagogical opportunities and risks of AI integration in Indonesian language learning. A Systematic Literature Review (SLR) was conducted following PRISMA guidelines, drawing on reputable scholarly articles related to AI, language pedagogy, and education within the Indonesian context. The findings indicate that AI can enrich Indonesian language learning when positioned as a supportive tool within a reflective pedagogical framework. However, risks such as students’ cognitive dependency, decline in authentic language production, digital literacy gaps, and linguistic and cultural biases must be carefully addressed. This study concludes that the effectiveness of AI integration largely depends on teachers’ pedagogical competence, critical instructional approaches, and institutional policies governing AI use. The results provide a conceptual foundation for developing responsible AI-based practices and policies in Indonesian language education.